2009
DOI: 10.1089/cap.2009.0035
|View full text |Cite
|
Sign up to set email alerts
|

Aripiprazole in Children and Adolescents with Tourette's Disorder: An Open-Label Safety and Tolerability Study

Abstract: Objective: The aim of this study was to conduct a prospective safety and tolerability study of aripiprazole for the treatment of tics in children and adolescents with Tourette's disorder (TD). Method: Eleven subjects (10 males) with TD (age 9-19 years, mean 13.36, standard deviation [SD] 3.33) who did not respond or were unable to tolerate previous tic medication were treated with aripiprazole in an open-label, flexible-dosing study over 10 weeks. Tic severity was rated using the Yale Global Tic Severity Scale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
44
0
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(53 citation statements)
references
References 30 publications
8
44
0
1
Order By: Relevance
“…Our fi ndings are consistent with those of Lyon et al [ 35 ] , who reported that the eff ect size of aripiprazole was d = 0.59 for hyperactivity and d = 0.47 for attention defi cits. In another study conducted with youths with juvenile bipolar disorder comorbid with ADHD, however, the eff ect size of aripiprazole at improving ADHD symptoms was d = 1.05, which is much higher than our fi ndings [ 16 ] .…”
Section: Tolerability Assessmentsupporting
confidence: 92%
“…Our fi ndings are consistent with those of Lyon et al [ 35 ] , who reported that the eff ect size of aripiprazole was d = 0.59 for hyperactivity and d = 0.47 for attention defi cits. In another study conducted with youths with juvenile bipolar disorder comorbid with ADHD, however, the eff ect size of aripiprazole at improving ADHD symptoms was d = 1.05, which is much higher than our fi ndings [ 16 ] .…”
Section: Tolerability Assessmentsupporting
confidence: 92%
“…Specifically, two large ARI studies in adolescents were not included in the statistical analyses because they had reported no baseline PRL values (Findling et al 2008a) or only incomplete PRL posttreatment findings (Finding et al 2009b). Furthermore, other PRL level findings on adolescents after treatment with ARI (Lyon et al 2009;Erickson et al 2011) had too few subjects (n = 23). Nonetheless, from the two large published trials, the percent of adolescents treated with ARI having subnormal PRL serum levels (< 3 ng/mL for females and < 2 ng/mL for males) had been reported, and these percentages were used for age group comparisons of PRL serum levels.…”
Section: Methodsmentioning
confidence: 96%
“…In children and adolescents, the washout of these drugs prior to the baseline laboratory assessments usually ranged from 3 days to 2 weeks; but there were some allowances for continued drug use. For example, three clinical trials of ARI allowed continuing selective serotonin reuptake inhibitor (SSRI) antidepressant drugs (Lyon et al 2009;Marcus et al 2011;Stigler et al 2012). The effect of SSRIs on serum PRL has been inconsistent, with some reporting a slight increase (Foley and Kast 2006), whereas others failed to note this change (Saito et al 2004;Calarge et al 2009).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pimozide, sertraline and aripiprazole are used for the treatment of pervasive developmental disorders [22][23][24][25][26]. Among them, pimozide is associated with prolongation of the QT interval, even at a low daily dosage, and has been implicated in cases of sudden death [27][28][29].…”
Section: Discussionmentioning
confidence: 99%